Association Between Use of Statins and Outcomes in Heart Failure With Reduced Ejection Fraction: Prospective Propensity Score Matched Cohort Study of 21 864 Patients in the Swedish Heart Failure Registry. (March 2015) - Alehagen, Urban; Benson, Lina; Edner, Magnus; Dahlström, Ulf; Lund, Lars H.
Abstract : Background—: In heart failure (HF) with reduced ejection fraction, randomized trials of statins did not demonstrate improved outcomes. However, randomized trials may not always be generalizable. The aim was to determine whether statins are associated with improved outcomes in an unselected nationwide population of patients with HF with reduced ejection fraction overall and in relation to ischemic heart disease (IHD). Methods and Results—: In the Swedish Heart Failure Registry, 21 864 patients with HF with reduced ejection fraction (age ± SD, 72±12 years; 29% women), of whom 10 345 (47%) were treated with statins, were studied. Propensity scores for statin use were derived from 42 baseline variables. The associations between statin use and outcomes were assessed with Cox regressions in a population matched 1:1 based on propensity score and age and in the overall population with adjustment for propensity score and age. The primary outcome was all-cause mortality; secondary outcomes were cardiovascular mortality; HF hospitalization; and combined all-cause mortality or cardiovascular hospitalization. Survival at 1 year in the matched population was 83% for statin-treated versus 79% for untreated patients (hazard ratio, 0.81; 95% confidence interval, 0.76–0.86; P <0.001). In the unmatched population, 1-year survival was 85% for statin-treated versus 79% for untreated patients, hazard ratio after adjustment for propensity score and age was 0.84 (95% confidence interval, 0.80–0.89; P <0.001). No examined baseline variables interacted with statin use except for IHD ( P =0.001), with a hazard ratio of 0.76 (95% confidence interval, 0.70–0.82, P <0.001) with IHD and 0.95 (95% confidence interval, 0.85–1.07; P =0.430 without IHD. Statin use was also associated with reduced risk for all 3 secondary outcomes. Conclusions—: In an unselected nationwide population of patients with HF with reduced ejection fraction, statins were associated with improved outcomes, specifically in the presence of IHD. This contrasts with previous randomized controlled trials. Additional randomized controlled trials with more generalized inclusion or focused on IHD may be warranted.